2021
DOI: 10.22541/au.161649872.26331755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review of CFTR Modulators 2020

Abstract: CFTR (cystic fibrosis transmembrane conductance regulator) modulators are small molecules that directly change the CFTR protein, improving function of the CFTR chloride channel. Beginning in 2012 with the FDA approval of the first CFTR modulator, ivacaftor, this class of medication has had largely positive effects on many outcomes in people with cystic fibrosis (pwCF), including lung function, quality of life, and growth. There have been continued exciting developments in the current research on CFTR modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Using the lung clearance index (LCI) as a parameter, decline is defined as annual drop of 17% and 15% in CF patients younger and older than 12 years of age, respectively [21,22]. "Improving lung function" is the sub-scenario in CF patients on treatment with new CF transmembrane conductance regulator (CFTR) modulator therapies [23]. In young children who cannot perform lung function tests, decline was defined by clinically integrated evaluation which included the presence of chronic respiratory symptoms, frequency of respiratory exacerbation and antibiotic therapy [24,25].…”
Section: Clinical Scenarios Imaging Modalities and Definitionsmentioning
confidence: 99%
“…Using the lung clearance index (LCI) as a parameter, decline is defined as annual drop of 17% and 15% in CF patients younger and older than 12 years of age, respectively [21,22]. "Improving lung function" is the sub-scenario in CF patients on treatment with new CF transmembrane conductance regulator (CFTR) modulator therapies [23]. In young children who cannot perform lung function tests, decline was defined by clinically integrated evaluation which included the presence of chronic respiratory symptoms, frequency of respiratory exacerbation and antibiotic therapy [24,25].…”
Section: Clinical Scenarios Imaging Modalities and Definitionsmentioning
confidence: 99%
“…It has been shown that ivacaftor, lumacaftor, and tezacaftor (used singly or in combination) are safe and efficacious in children aged 6–11 years 5 . Furthermore, the results of a 24‐week, Phase‐III open‐label trial of ETI have shown that the treatment was as safe and effective in CF patients aged 6–11 years with at least one F508del allele as in adults and adolescents 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There are over 2000 known mutations across a number of mutation classes that result in a heterogenous phenotype, ranging from classic pancreatic insufficient CF to CFTR related diseases and even no evidence of disease despite mutations in each allele 1 . The diagnosis of CF can be challenging for those who do not have typical symptoms, and this can raise issues about how they should be managed and whether it is appropriate to use CFTR modulators 2,3 …”
Section: Introductionmentioning
confidence: 99%